Project Report on Experimental Studies on Magnetostrictive Composites - HARINATH M V (2005)
INTERNAL GUIDE: A AROKKIASWAMY, MVJCE EXTERNAL GUIDE: G SHIVAGNANAM, SCINTIST E, CENTRE FOR AIRBORNE SYSTEM
Keywords: Magnetostrictive Composites